Canvas and marketing tools as assumptions for managerial decision making (Research, Society and Development, 2022)
The main objective of this work was to propose a model of actions and steps helping managers and organizations in sustainable decision making and better managerial and commercial competitiveness. For this, a bibliometric research was carried out in the database Periódico Capes (2021), and no scientific or academic works were found with a proposal to relate both themes in the study of marketing or commercial management. The theoretical contribution of the work was to bring an updated literature to support the interface between the proposed themes, in addition to describing the theoretical relationship between the marketing plan and the business model. The Canvas model is a tool that allows planning and analyzing organizational resources and has facilities such as visual exposure, simplicity, global approach, among others. And a marketing plan involves communication in an action designed by partners and investors to be directed to other internal and external stakeholders, such as internal managers, employees, business partners, and in some cases, current and prospective customers. The practical contribution of the work was to elaborate and describe a consolidated and self-applicable model in the organizational environment based on marketing and commercial elements present in the organization. The main conclusion was that the model still seems incipient, needing more support, application and validation for its widespread use.